Qualitative Analysis of an Implicit Singular Cauchy Problem - Zernov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider a singular Cauchy problem for a first-order ordinary differential equation unsolved with respect to the derivative of the unknown function. We prove the existence of continuously differentiable solutions with required asymptotic properties.